Cartilage structure-inspired nanofiber-hydrogel composite with robust proliferation and stable chondral lineage-specific differentiation function to orchestrate cartilage regeneration for artificial tracheal construction - Yaqiang Li; Xiaowei Xun; Liang Duan; Erji Gao; Jiaxin Li; Lei Lin; Xinping Li; Aijuan He; Haiyong Ao; Yong Xu; Huitang Xia (Bioactive Materials)
Tissue engineering strategies hold promise for constructing biomimetic tracheal substitutes to repair circumferential tracheal defects. However, current strategies for constructing off-the-shelf cartilage analogs for artificial trachea grafts face challenges of chondrocyte scarcity and inadequate culture strategies, which require extensive cell expansion and prolonged in vitro culture to generate robust neo-cartilage. To address these issues, we developed a nanofiber-hydrogel composite with superior mechanical performance by incorporating fragment oxidized bacterial cellulose (BC) nanofibers into a gelatin methacryloyl (GelMA) hydrogel network. Additionally, a biomaterial system was developed based on this composite, featuring dual-release functionality of fibroblast growth factor (FGF) and transforming growth factor beta (TGF-β) to facilitate step-wise maturation of neo-cartilage tissue. This process includes early-stage proliferation followed by second-stage extracellular matrix (ECM) deposition, driving the transition from proliferation to chondrogenesis. By encapsulating chondrocytes within the biomaterial system, mature neo-cartilage tissues with typical cartilage lacunae structures and abundant homogeneous cartilage-specific ECM deposition were successfully regenerated in vitro and in vivo. Furthermore, with a tailor-made growth factor-releasing strategy, the biomaterial system with low cell seeding density achieved biochemically and biomechanically functional neo-cartilage tissue regeneration, comparable to that achieved with high cell seeding density in the nanofiber-hydrogel composite. Based on the current biomaterial system, mature and functional cartilage-ring analogs were successfully constructed and applied to repair tracheal defects. Overall, the biomaterial system developed in this study provides a promising strategy for engineering transplantable, high-quality cartilage substitutes, with translational potential for artificial trachea construction.